Early diagnosis of genital mucosal melanoma: how good are our dermoscopic criteria? - Tova Rogers; Melissa Pulitzer; Maria L. Marino; Ashfaq A. Marghoob; Oliver Zivanovic; Michael A. Marchetti (Mattioli1885, 2016)
Background: There are limited studies on the dermoscopic features of mucosal melanoma, particularly early-stage lesions. Described criteria include the presence of blue, gray, or white colors, with a reported sensitivity of 100%. It is unclear if these features will aid in the detection of early mucosal melanoma or improve diagnostic accuracy compared to naked-eye examination alone. Case: An Asian female in her fifties was referred for evaluation of an asymptomatic, irregularly pigmented patch of the clitoral hood and labia minora of unknown duration. Her past medical history was notable for Stage IV non-small cell lung cancer. She denied a personal or family history of skin cancer. Dermoscopic evaluation of the vulvar lesion revealed heterogeneous brown and black pigmentation mostly composed of thick lines. There were no other colors or structures present. As the differential diagnosis included vulvar melanosis and mucosal melanoma, the patient was recommended to undergo biopsy, which was delayed due to complications from her underlying lung cancer. Repeat dermoscopic imaging performed three months later revealed significant changes concerning for melanoma, including increase in size, asymmetric darkening, and the appearance of structureless areas and central blue and pink colors. Histopathological examination of a biopsy and subsequent resection confirmed the diagnosis of melanoma in situ. Conclusion: Previously described dermoscopic features for mucosal melanoma may not have high sensitivity for early melanomas. Additional studies are needed to define the dermoscopic characteristics of mucosal melanomas that aid in early detection. Health care providers should have a low threshold for biopsy of mucosal lesions that show any clinical or dermoscopic features of melanoma, especially in older women.